Director pay slice, the remuneration committee, and firm financial performance - Nadia Klarita Rahayu; Iman Harymawan; Mohammad Nasih; John Nowland (Cogent Economics & Finance, 2022)
This study aimed to analyze the relationship between the director pay slice and firm financial performance. This study used 1024 observations from companies listed on the Indonesia Stock Exchange from 2011 to 2019. The analytical technique used in this study was ordinary least square regression with a cluster model approach and fixed effects using the STATA 16.0 software. This study partially found that director pay slice and the existence of a remuneration committee are positively and significantly related to the company's current and future performance. Furthermore, this study indicates that companies with a high director pay slice and remuneration committees tend to have a better level of performance because the presence of a remuneration committee helps to align the relationship between the director pay slice and firm financial performance. This study has implications for developing countries regarding effective corporate governance by analyzing the governance in Indonesia. Our study's overarching goal was to understand the relationship between the director's pay slice and the firm's financial performance through the overall analysis.
Keywords: M40; M41; M48; 330; Director pay slice; firm financial performance; remuneration committee; corporate governance